Effect of co-solvent addition on the reaction kinetics of the lipase-catalyzed resolution of ibuprofen ester - Gonawan, Fadzil; Lau, John; Kamaruddin, Azlina; Uzir, Mohamad (Wiley, 2013)
BACKGROUND: The addition of co-solvent is not limited to enhancing the catalytic rate, it could also assist in situ racemization in the dynamic kinetic resolution of racemic compounds by increasing the reactivity of the base catalyst employed. In the current work, reaction media with the presence of DMSO were investigated in Candida rugosa lipase (EC 3.1.1.3)-catalyzed hydrolysis of ibuprofen ester that focuses on the thermodynamic effect, reaction stability and implication for the kinetic parameters. RESULTS: The introduction of 2% DMSO increased the reaction rate, conversion, and enantioselectivity of the Candida rugosa lipase-mediated resolution. However, the performance of the particular enzymatic reaction was reduced when a higher DMSO concentration was added. At lower reaction temperatures, the medium with 2% DMSO exhibited an increase in enantioselectivity, which was attributed to a higher activation energy difference between the fast- and slow-reacting enantiomers compared with the water-isooctane medium. Additionally, the presence of DMSO had a significant effect on the kinetic parameters, shown by a lower value of Michaelis constant compared with that of a normal reaction without DMSO, which resulted in a fast reaction rate. Finally, inhibition due to the uncompetitive substrate inhibitor was reduced, while the non-competitive product inhibitor consequently increased. CONCLUSION: This work has demonstrated that only 2% of DMSO can be tolerated by the free Candida rugosa lipase in the resolution of ibuprofen ester. However, it is still able to give significant positive effects on the hydrolysis rate, kinetic parameters and enantioselectivity as well as reaction stability.